Effects of embedded trench installations using expanded polystyrene geofoam applied to buried corrugated steel arch structures. (April 2020) - Santos, Ralph Raymond V.; Kang, Junsuk; Park, Jong Sup
Highlights: Geofoam height significantly reduce the pressure, stress and deflection at the arch. Deep corrugated steel provides larger reduction around the arch for ETI (Embedded Trench Installation) models. Standard corrugated steel provides better reduction of stress and deflection for ITI (Imperfect Trench Installation) ETI models provides better reduction in pressure especially at the spring line. ITI models provides better reduction in stress and deflection around the arch. Abstract: Over the years, considerable progress have been made for the improvement of the design criteria of buried culverts that increased in size and numbers with the development of information and technology in this field. This research investigates the effects of trench installation methods with expanded polystyrene (EPS) geofoam on the behavior of buried corrugated steel arch structure. A finite element analysis program, ABAQUS, was used to model and analyze the structure. For this study, an S275 corrugated steel with profiles of 152 × 51mm and 400 × 150mm, and thickness ranging from 3 mm to 7 mm was used. The structure was analyzed for three different configurations, namely; initial (without EPS geofoam), imperfect trench installation (ITI), and embedded trench installation (ETI) through three parametric analysis considering the influence of EPS geofoam's geometry, thickness and corrugation profile of steel. The results from the finite element analyses revealed that ETI models reduced the earth pressure, deflection, and stress at the crown by 68%, 40%, and 39% on the average. It is recommended to conduct further study regarding ETI to validate the results and to further improved the design criteria of buried corrugated steel arch as it is expected to bring about cost reduction and stability for buried structures.